2007
DOI: 10.21273/hortsci.42.5.1135
|View full text |Cite
|
Sign up to set email alerts
|

Toward Breeding for Resistance to Fusarium Tuber Rot in Caladium: Inoculation Technique and Sources of Resistance

Abstract: Fusarium tuber rot, incited by Fusarium solani, is the major cause of losses of tuber quality and quantity in caladium (Caladium ×hortulanum) during storage and production. To develop a reliable inoculation method for evaluating cultivar susceptibility to Fusarium tuber rot and identifying sources of resistance, the effect of temperature on the mycelial growth of F. solani in vitro and on tuber r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
18
0

Year Published

2008
2008
2019
2019

Publication Types

Select...
5
3

Relationship

4
4

Authors

Journals

citations
Cited by 18 publications
(18 citation statements)
references
References 9 publications
0
18
0
Order By: Relevance
“…Saa. (Goktepe et al, 2007), pythium root rot caused by Pythium myriotylum Drechs. (Deng et al, 2005a), and root-knot nematodes [Meloidogyne incognita (Kofoid and White) Chitwood] (Dover et al, 2005;McSorley et al, 2004).…”
Section: Methodsmentioning
confidence: 99%
“…Saa. (Goktepe et al, 2007), pythium root rot caused by Pythium myriotylum Drechs. (Deng et al, 2005a), and root-knot nematodes [Meloidogyne incognita (Kofoid and White) Chitwood] (Dover et al, 2005;McSorley et al, 2004).…”
Section: Methodsmentioning
confidence: 99%
“…Preliminary results (data not shown) showed that this cultivar was susceptible to both diseases. This was expected as both parents of 'Sea Foam Pink' ('Carolyn Whorton' and 'Miss Muffet') were susceptible or highly susceptible to Fusarium tuber rot and Pythium root rot (Deng et al, 2005a(Deng et al, , 2005bGoktepe et al, 2007).…”
Section: Possible Susceptibility To Pythium Root Rot and Fusarium Tubmentioning
confidence: 85%
“…They are caused by Pythium myriotylum and Fusarium solani, respectively. The majority of caladium cultivars in commercial production are susceptible to these diseases (Deng et al, 2005a(Deng et al, , 2005bGoktepe et al, 2007). 'Sea Foam Pink' was tested for susceptibility to Pythium root rot and Fusarium tuber rot in 2014.…”
Section: Possible Susceptibility To Pythium Root Rot and Fusarium Tubmentioning
confidence: 99%
“…x The resistance levels of these commercial cultivars were reported by Goktepe et al (2007). NS Not significantly different at P < 0.05.…”
Section: Cultivarmentioning
confidence: 99%
“…Resistance to Fusarium Tuber Rrot 'Icicle' was compared with selected caladium cultivars regarding its susceptibility to Fusarium tuber rot. Caladium tubers of 'Icicle' and commercial cultivars Candidum, Carolyn Whorton, Freida Hemple, Red Flash, and White Christmas were surface-sterilized, cut in half, and inoculated with Fusarium solani by inserting two pieces of Fusariumcolonized carnation leaf segments (Goktepe et al, 2007). Inoculated tuber halves were placed inside egg cartons and incubated at 18°C under 100% relative humidity.…”
mentioning
confidence: 99%